Transthyretin amyloidosis and herpes zoster infection: a mimic of temporal arteritis - Riley, Mark (BMJ Case Rep, 2021)
We describe the case of a patient who presented with symptoms of persistent headaches, left-sided facial pain and blurry vision of the left eye. The patient had recovered from a herpes zoster infection of the V1 division of the trigeminal nerve 1 month prior. Serum inflammatory markers were elevated, raising concern for temporal arteritis. Empiric high-dose prednisone was initiated. Bilateral temporal artery biopsies were performed but did not show evidence of vasculitis or multinucleated giant cells. Instead, extracellular material deposits were present within the vessel walls. Congo red staining was diagnostic for amyloidosis. Liquid chromatography and mass spectrometry identified the amyloid fibrils to be transthyretin-type (ATTR) consistent with age-related amyloidosis. Temporal artery involvement of amyloidosis is rare but when present is most often due to light chain amyloidosis. Based on our review of the literature, only a few cases of temporal artery ATTR amyloidosis have been reported.